2021
DOI: 10.3390/foods10030520
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Fat Crystal Polymorphism in Cocoa Butter by Time-Domain NMR and DSC Deconvolution

Abstract: The polymorphic state of edible fats is an important quality parameter in fat research as well as in industrial applications. Nowadays, X-ray diffraction (XRD) is the most commonly used method to determine the polymorphic state. However, quantification of the different polymorphic forms present in a sample is not straightforward. Differential Scanning Calorimetry (DSC) is another method which provides information about fat crystallization processes: the different peaks in the DSC spectrum can be coupled to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…CB is mainly composed of 23.2–29.3% 1,3-di-stearoyl-2-oleoyl-glycerol (SOS), 34.2–38.6% 1-palmitoyl-2-oleoyl-3-stearoyl-glycerol (POS), and 13.5–17.1% 1,3-dipalmitoyl-2-oleoylglycerol (POP) [ 9 , 10 ]. These TAGs allow CB to crystallize in six polyforms, which are γ, α, ′, , , and , and are identified according to their melting temperatures (17.3, 23.3, 25.5, 27.5, 33.8, and 36.3 °C; respectively) [ 9 , 11 , 12 , 13 , 14 ] and stability. Although the contribution of POP is less than those of POS and SOS, its presence may influence the formation of metastable polymorphic forms in CB [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CB is mainly composed of 23.2–29.3% 1,3-di-stearoyl-2-oleoyl-glycerol (SOS), 34.2–38.6% 1-palmitoyl-2-oleoyl-3-stearoyl-glycerol (POS), and 13.5–17.1% 1,3-dipalmitoyl-2-oleoylglycerol (POP) [ 9 , 10 ]. These TAGs allow CB to crystallize in six polyforms, which are γ, α, ′, , , and , and are identified according to their melting temperatures (17.3, 23.3, 25.5, 27.5, 33.8, and 36.3 °C; respectively) [ 9 , 11 , 12 , 13 , 14 ] and stability. Although the contribution of POP is less than those of POS and SOS, its presence may influence the formation of metastable polymorphic forms in CB [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the analytical technique of X-ray diffraction (XRD) is the most used to study the polymorphism of fat crystals. However, access to XRD equipment is not easy in a research and development unit, so differential scanning calorimetry (DSC) [ 12 ] is an alternative. MacNaughtan et al [ 37 ] demonstrated that the DSC technique could provide reproducible kinetic data on the tristearin-tripalmitin crystallization and polymorphism.…”
Section: Introductionmentioning
confidence: 99%
“…It allows the characterization of atomic and molecular structures of materials by evaluating parameters such as crystallite size and lattice strain. In the food industry, XRD is extensively used to investigate the polymorphism of fats, which refers to the different crystal arrangements of the long hydrocarbon chains in fats [68][69][70]. The three most commonly observed polymorphic structures in fats are α, β , and β, in increasing order of stability [71].…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…Repeated temperature cycling of butter products from refrigerated to room conditions allows the conversion of a metastable state to a more stable form (β), being adversely affected in the process of spreadability [ 9 ]. For spreadable fats, small β′ crystals are favored since they enable the formation of a good crystal network throughout the continuous lipid phase which is related to desirable sensory and textural properties [ 10 ].…”
Section: Introductionmentioning
confidence: 99%